Eksplorasi Nilai-Nilai Kearifan Lokal dalam Praktik Pembelajaran Kooperatif di Kelas IV Sekolah Dasar - Muhammad Jordi; Ari Suriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study is to examine the values of local wisdom when used in cooperative learning in fourth grade elementary school classrooms. Contextual learning that aligns with students’ cultural environment plays a crucial role in enhancing their engagement in the learning process. This study uses qualitative and descriptive methods. Data collection methods include documentation, in-depth interviews, and observation. This study explores the integration of local cultural values—such as consultation, mutual assistance, mutual respect, and traditional games in cooperative learning. The results show that applying local wisdom in cooperative learning can improve the learning atmosphere, create better social interaction, and increase student participation. The results indicate that local wisdom can serve as a strong foundation for building learning that is relevant, contextual, and rooted in students' culture.